The Effect of Individual Entrepreneurial Orientation on Student’s Entrepreneurial Intention in West Kalimantan - Wahyudi, Raymond (HM Publisher, 2023)
Entrepreneurship has become one of the main issues in government policy in various countries. Therefore, understanding entrepreneurial intention (EI) and individual entrepreneurial orientation (IEO) is important for research. EI is influenced by many factors, such as social environment and cultural and psychological factors. IEO is an individual personality characteristic that reflects a tendency to engage in entrepreneurial behavior with three dimensions, namely, innovative, proactive, and risk-taking. However, there has not been much research on IEO and EI in the context of vocational students. So, through this research, the relationship between IEO and EI for vocational students in Indonesia will be explained in detail. This study involved 388 vocational students in West Kalimantan. The participants were randomly selected and analyzed using quantitative methods to test the proposed hypothesis. Based on the results of the study, it was found that there was a positive and significant relationship between the dimensions of IEO on EI both directly and indirectly. The implications of the results of this research are that agencies and governments tasked with developing entrepreneurial ecosystems must understand the importance of IEOs in increasing EI. Therefore, policies and programs must be designed to develop IEOs and create a conducive environment for individuals to develop as entrepreneurs. However, this study had several limitations. First, this study only involved students from one vocational school. Therefore, the research findings may not necessarily be applicable to large populations. Second, this study used quantitative methods, so it did not explain in depth the individual experiences in forming EI.